Insights into the increased degradation rate of CH3NH3PbI3 solar cells in combined water and O2 environments. Issue 48 (29th November 2017) - Aristidou, Nick; Eames, Christopher; Islam, M. Saiful; Haque, Saif A.
Abstract : Halide perovskites offer low cost and high efficiency solar cell materials but serious issues related to air and moisture stability remain. Abstract : Halide perovskites offer low cost and high efficiency solar cell materials but serious issues related to air and moisture stability remain. In this study we show, using UV-vis, fluorescence and time of flight secondary ion mass spectrometry (ToF-SIMS) techniques, that the degradation of methylammonium lead iodide solar cells is significantly accelerated when both air and moisture are present in comparison to when just air or moisture is present alone. Using ab initio computational techniques we identify the thermodynamic driving force for the enhanced reactivity and highlight the regions of the photoexcited material that are the most likely reaction centres. We suggest that water catalyses the reaction by stabilising the reactive superoxide species, enabling them to react with the methylammonium cation.